Multimedia Programming with Pure Data. - Chung, Bryan WC (Packt Publishing, 2013)
A quick and comprehensive tutorial book for media designers to jump-start interactive multimedia production with computer graphics, digital audio, digital video, and interactivity, using the Pure Data graphical programming environment. An introductory book on multimedia programming for media artists/designers who like to work on interactivity in their projects, digital art/design students who like to learn the first multimedia programming technique, and audio-visual performers who like to customize their performance sets.